A mixed adhesion–brittle fracture model and its application to the numerical study of ice shedding mechanisms. (June 2016) - Bennani, L.; Villedieu, P.; Salaun, M.
Graphical abstract: Highlights: A coupled brittle failure/adhesive debonding model is proposed. Mechanical properties for atmospheric ice are identified. Several ice shedding mechanisms are proposed. Numerical investigation shows possibility of a mixed mode ice shedding mechanism. Thick ice shapes are predicted to be harder to remove although inducing a higher pressure differential. Abstract: The understanding of ice shedding is of prime importance in the assessment of aeronautical ice protection systems. In this paper, the authors previously studied mechanism is extended to include adhesive debonding. It is based on pressure redistribution in the water film formed at the ice/airfoil interface. The numerical modelling of crack propagation is based on recent work on damage mechanics which provides a general framework. As for adhesive debonding an algebraic model is derived from general mechanical equilibrium relations. Numerical experiments are performed to study an adhesive-debonding/brittle-failure mode detachment, the results of which are discussed.